Marketing Mix of Dry Bulk Market Share at Jamrud Terminal - Dian Arisanti; Mudayat Mudayat; Isabela Kilimandu (LPPM of NAROTAMA UNIVERSITY, 2022)
Purpose: The purpose of this study is to find out and analyze how the marketing mix affects the market share of loading and unloading dry bulk at Jamrud Terminal. Design / methodology / approach: The method in this study uses a quantitative approach with multiple linear regression analysis Findings: The research is conducted on the service users of Jamrud Terminal Research limitations / implications: This study is only limited by using four independent variables and one dependent variable. The independent variables are product, price, promotion and place. The dependent variable is market share Practical Implications: The population is 54 employees determined by the Slovin formula and random sampling. Originality / Value: This research is conducted at a company using port service at Jamrud Terminal. Paper type: Research paper